2023
DOI: 10.1007/s10644-022-09472-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty, governance institutions and economic performance in Africa: are there regional differences?

Abstract: In recent years, the global economy has witnessed several uncertainty-inducing events. However, empirical evidence in Africa on the effects of economic policy uncertainty (EPU) on economic activities remains scanty. Besides, the moderating effect of governance institutions on the uncertainty-economic performance relationship in Africa and the likelihood of regional differences in the response of economic activities to EPU on the continent are yet to be investigated. To address these gaps, we applied system GMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…This finding is consistent with some studies ( e.g . Caggiano et al, 2020; Čižmešija et al, 2017; Ekeocha et al, 2023; Kang et al, 2020; Mumtaz & Musso, 2021; van Robays, 2016) that have also established that uncertainty impacts negatively on economic activities. Clearly, this finding is consistent with the realities of African economies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with some studies ( e.g . Caggiano et al, 2020; Čižmešija et al, 2017; Ekeocha et al, 2023; Kang et al, 2020; Mumtaz & Musso, 2021; van Robays, 2016) that have also established that uncertainty impacts negatively on economic activities. Clearly, this finding is consistent with the realities of African economies.…”
Section: Resultsmentioning
confidence: 99%
“…Following the Global Terrorism Report of the Institute for Economics and Peace (IEP, 2022), the count of fatalities resulting from terrorist attacks within a particular year represents terrorism fatalities, whereas the number of terrorist incidents occurring in a given year represents terrorism incidence. In this study, we followed Ekeocha et al (2021) and Ekeocha et al (2023) by computing economic policy uncertainty using the simple arithmetic average of the corresponding 12 monthly values. This study also includes other control variables that have been identified as determinants of economic complexity in the extant literature, including trade openness (% GDP), international tourism (number of arrivals), physical capital stock and institutional quality (Nguyen et al, 2020; Saadi, 2020; Vu, 2022; Wiredu et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ekeocha et al (2023),Ogbonna et al (2022), andOgbuabor et al (2023b) by formulating a dynamic panel data model as follows:…”
mentioning
confidence: 99%